The Effect of Working Capital Management Efficiency on Profitability of Pharmaceutical Companies on the Indonesia Stock Exchange - Jumaidah Apriani Limbong (Institute of Computer Science (IOCS), 2021)
This study aims to identify and analyze the influence of working capital management efficiency (Inventory Conversion Period, Receivable Collection Period, Payables Defferal Period, Cash Conversion period, Firm Size, and Company status) together and partially to Profitability On Pharmaceutical Companies Listed In Indonesia Stock Exchange. The data analysis technique used is multiple linear analysis with pooled least square method. The population in this study were 8 Pharmaceutical Companies year 2010-2014 there are Companies BUMN and BUMS. samples were taken based on certain criteria. based on these criteria the number of samples of this study of eight Pharmaceutical Companies. the results of this study indicate that together working capital management efficiency that consist of Inventory Conversion Period, Receivable Collection Period, Payables Defferal Period, Cash Conversion period, Firm Size, and Company status significantly influence to Profitability. However, partial, Inventory Conversion Period, dan Receivable Collection Period not significant positive effect on Gross Profit Margin. Payables Defferal Period, dan Cash Conversion period not significant negative effect on Gross Profit Margin, Firm Size, significant negative effect on Gross Profit Margin, and company status significant positive effect on Gross Profit Margin.